Anticancer properties of bacterial cellulose membrane containing ethanolic extract of Epilobium angustifolium L - Perużyńska, Magdalena; Nowak, Anna; Birger, Radosław; Ossowicz-Rupniewska, Paula; Konopacki, Maciej; Rakoczy, Rafał; Kucharski, Łukasz; Wenelska, Karolina; Klimowicz, Adam; Droździk, Marek; Kurzawski, Mateusz (Frontiers in Bioengineering and Biotechnology, 2023)
Epilobium angustifolium L. is a medicinal plant well known for its anti-inflammatory, antibacterial, antioxidant, and anticancer properties, related to its high polyphenols content. In the present study, we evaluated antiproliferative properties of ethanolic extract of E. angustifolium (EAE) against normal human fibroblasts (HDF) and selected cancer cell lines, including melanoma (A375), breast (MCF7), colon (HT-29), lung (A549) and liver (HepG2). Next, bacterial cellulose (BC) membranes were applied as a matrix for the controlled delivery of the plant extract (BC-EAE) and characterized by thermogravimetry (TG), infrared spectroscopy (FTIR), and scanning electron microscopy (SEM) images. In addition, EAE loading and kinetic release were defined. Finally, the anticancer activity of BC-EAE was evaluated against the HT-29 cell line, which presented the highest sensitivity to the tested plant extract (IC50=61.73 ± 6.42 µM). Our study confirmed the biocompatibility of empty BC and the dose and time-dependent cytotoxicity of the released EAE. The plant extract released from BC-2.5%EAE significantly reduced cell viability to 18.16% and 6.15% of the control values and increased number apoptotic/dead cells up to 37.53% and 66.90% after 48 and 72 h of treatment, respectively. In conclusion, our study has shown that BC membranes could be used as a carrier for the delivery of higher doses of anticancer compounds released in a sustained manner in the target tissue.